The Influence of Tax Awareness, Tax Understanding, Tax Sanctions on Land and Building Taxpayer Compliance: (Case Study in Rumpin District) - Hikma, Nur; Juitania (EAJ (Economic and Accounting Journal), 2024)
This research examines the influence of tax awareness, tax understanding, and tax sanctions on taxpayer compliance in paying land and building taxes. This research uses primary data with samples distributing questionnaires. The sampling technique used the Slovin formula, with the number of questionnaires distributed to 400 respondents. The dependent or dependent variable in this research is land and building tax compliance. The independent or independent variables in this research are tax awareness, tax understanding, and tax sanctions. The data analysis methods used are descriptive statistical analysis test, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test (R2), simultaneous test (F), and partial test (T ) using the SPSS version 23 data processing program. The reason the researcher chose the research object in Rumpin District is because based on data from the Regional Revenue Agency at the Parung Class A Regional Tax Technical Implementation Unit from 2019 to 2023, data from tax realization in the Rumpin District area, Bogor Regency, shows that the Rumpin District's realization and tax assessment have not been able to reach target. In this way, researchers will examine the factors that influence tax awareness, tax understanding, and tax sanctions on land and building tax compliance.   Keywords:Taxpayer Compliance; Tax Awareness; Tax Understanding; Tax Sanctions